Seasonal patterns of malaria, genital infection, nutritional and iron status in non-pregnant and pregnant adolescents in Burkina Faso: a secondary analysis of trial data - Stephen A. Roberts; Loretta Brabin; Halidou Tinto; Sabine Gies; Salou Diallo; Bernard Brabin (BMC, 2021)
Abstract Background Adolescents are considered at high risk of developing iron deficiency. Studies in children indicate that the prevalence of iron deficiency increased with malaria transmission, suggesting malaria seasonally may drive iron deficiency. This paper examines monthly seasonal infection patterns of malaria, abnormal vaginal flora, chorioamnionitis, antibiotic and antimalarial prescriptions, in relation to changes in iron biomarkers and nutritional indices in adolescents living in a rural area of Burkina Faso, in order to assess the requirement for seasonal infection control and nutrition interventions. Methods Data collected between April 2011 and January 2014 were available for an observational seasonal analysis, comprising scheduled visits for 1949 non-pregnant adolescents (≤19 years), (315 of whom subsequently became pregnant), enrolled in a randomised trial of periconceptional iron supplementation. Data from trial arms were combined. Body Iron Stores (BIS) were calculated using an internal regression for ferritin to allow for inflammation. At recruitment 11% had low BIS (< 0 mg/kg). Continuous outcomes were fitted to a mixed-effects linear model with month, age and pregnancy status as fixed effect covariates and woman as a random effect. Dichotomous infection outcomes were fitted with analogous logistic regression models. Results Seasonal variation in malaria parasitaemia prevalence ranged between 18 and 70% in non-pregnant adolescents (P < 0.001), peaking at 81% in those who became pregnant. Seasonal variation occurred in antibiotic prescription rates (0.7-1.8 prescriptions/100 weekly visits, P < 0.001) and chorioamnionitis prevalence (range 15-68%, P = 0.026). Mucosal vaginal lactoferrin concentration was lower at the end of the wet season (range 2-22 μg/ml, P < 0.016), when chorioamnionitis was least frequent. BIS fluctuated annually by up to 53.2% per year around the mean BIS (5.1 mg/kg2, range 4.1-6.8 mg/kg), with low BIS (< 0 mg/kg) of 8.7% in the dry and 9.8% in the wet seasons (P = 0.36). Median serum transferrin receptor increased during the wet season (P < 0.001). Higher hepcidin concentration in the wet season corresponded with rising malaria prevalence and use of prescriptions, but with no change in BIS. Mean Body Mass Index and Mid-Upper-Arm-Circumference values peaked mid-dry season (both P < 0.001). Conclusions Our analysis supports preventive treatment of malaria among adolescents 15-19 years to decrease their disease burden, especially asymptomatic malaria. As BIS were adequate in most adolescents despite seasonal malaria, a requirement for programmatic iron supplementation was not substantiated.